Asepsis during periodontal surgery involving oral implants and the usefulness of peri-operative antibiotics: a prospective, randomized, controlled clinical trial - Mahmoud Abu-Ta’a, (2008)
Objectives: This randomized clinical trial compares the usefulness of pre- and postoperative antibiotics while strict asepsis was followed during periodontal surgery. Material and Methods: Two groups of 40 consecutive patients each with fully or partially edentulous jaws were enrolled. Antibiotics group (GrAB1): 23 men, mean age 60, 128 implants, received oral amoxicillin 1 g, 1 h pre-operatively and 2 g for 2 days post-operatively. Non-antibiotics group (GrAB ): 20 men, mean age 57, 119 implants, received no antibiotics. Bacterial samples were taken from the peri-oral skin before and at the end of surgery. In 12 patients in each group, samples were also taken from the nares. A VAS questionnaire evaluated symptoms of infection/ inflammation by both the patient and the periodontologist at suture removal. Results: There were no significant differences between both groups, neither for the clinical parameters nor for the microbiota. Staphylococcus aureus was detected in the nares of one patient only. The patients’ subjective perception of post-operative discomfort was significantly smaller in the group receiving antibiotics. Three patients lost one or two implants. Conclusions: Antibiotics do not provide significant advantages concerning postoperative infections in case of proper asepsis. It also does not reduce peri-oral microbial contamination. It does on the other hand reduce post-operative discomfort.